2008
DOI: 10.5539/ies.v1n2p3
|View full text |Cite
|
Sign up to set email alerts
|

Bases of Power and Subordinates’ Satisfaction with Supervision - The Contingent Effect of Educational Orientation

Abstract: The study seeks to find out the impact of the supervisory power bases on subordinates' satisfaction with supervision in industrial settings. The influence of educational orientations of superiors and subordinates was also examined. The results indicated that referent power, expert power and reward power showed positive relationship with satisfaction with supervision. In terms of rank ordering of bases of power, referent power ranked the highest among other power exercises. This was followed by expert and rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…The positive relationship between expert power and intention to commit a crime of obedience indicated that expert power is not used effectively in government academic organizations of Pakistan. Positive impact on team productivity can be observed if expert power is to be used effectively (Lee, 2008). Results indicated that respondents provide the high mean value of expert power variable but the same time, they show more intentions to obey leader's immoral demand.…”
Section: Hypothesis Testingmentioning
confidence: 97%
See 1 more Smart Citation
“…The positive relationship between expert power and intention to commit a crime of obedience indicated that expert power is not used effectively in government academic organizations of Pakistan. Positive impact on team productivity can be observed if expert power is to be used effectively (Lee, 2008). Results indicated that respondents provide the high mean value of expert power variable but the same time, they show more intentions to obey leader's immoral demand.…”
Section: Hypothesis Testingmentioning
confidence: 97%
“…Luthans (2011) stated that before exercise the expert power, followers must perceive the power-holders as honest, relevant and credible. Expert power has an importance for acceptance the supervisor direction among technical staff (Lee, 2008). The ability to persuade others based on admiration, respect, loyalty and affection is referent power (Craig and Dauglas, 2006).…”
Section: Expert Power and Intention To Commit A Crimementioning
confidence: 99%
“…This theoretical framework was developed from literature and findings of different studies. It was basically based on Lee, and Low (2008) power bases and job satisfaction theoretical framework. The model shows that six power bases are related to job satisfaction.…”
Section: Hypotheses To Be Testedmentioning
confidence: 99%
“…However, studies on power bases and job satisfaction have shown mixed results. Afza, (2005) and Lee and Low (2008) for example, revealed that referent power, expert power and reward power showed a positive relationship with satisfaction (Ogunleye, Odebiyi, & Olaoye, 2013). On the other hand, Nedaee, Alavi, K. and Ramezani (2012) suggested that no significant relationship was obtained between the two variables.…”
mentioning
confidence: 99%
“…Literature shows that leadership style affects job performance and job satisfaction. For instance, employees who are generally over-controlled by the supervisor and are recipients of penalties and warnings rather than coaching and feedback, generally feel low job satisfaction (Lee, 2008). Therefore, in this study, the direct effect of leadership style is investigated in the context of Jordanian audit firms, where the hypotheses proposed for testing in this relationship state;…”
Section: Leadership Styles and Job Satisfactionmentioning
confidence: 99%